SEBUAH IDE TENTANG BIROKRASI MASA DEPAN - RINA MARTINI, RINA MARTINI (Program Magister Ilmu Politik, Universitas Diponegoro, 2011)
AbstractBureaucracy is still the organization that is needed by all levels of society. Therefore, itsexistence should be retained. But it just is not enough to maintain, must be accompanied by a goodtrade mark. Currently bureaucratic organizations still clung to as the politicization of the bureaucracyin order to perpetuate the power of officials. Efforts to improve or reform has been a lot done, but notyet achieved the expected results. Future form of bureaucracy that is able to be servants to thecommunity, highly anticipated. That is the bureaucracy that serves the community with a friendly,open to criticism, and not picky, responsible for the task, and resilient to face the challenges ofinternal and external.Key word : bureaucracy of the present,idea,bureaucracy present.